The formation and evolution of massive galaxies and their supermassive black holes over the past 12 billion years - Bluck, Asa Frederick Leon (2011)
This thesis examines many of the ways in which massive galaxies and their super- massive black holes have changed over the past 12 billion years. In a sense, this is an attempt to write a cosmic history of massive galaxies, and in so doing construct a useful catalogue of changes which can be studied to gain insight into galaxy formation and evolution. In particular, this thesis concentrates on two potential drivers for galactic evolution: external influences from galaxy - galaxy interactions (Chapters 2 - 3); and internal influences from AGN feedback (Chapter 4). We find that both of these mechanisms have a profound impact on massive galaxies throughout their lifetimes.